Makna Kebahagiaan dalam Pembelajaran Guru terhadap Anak Didik di Sekolah - Mujahid, Kasori; Nuryahya, Ikhsan (TSAQOFAH, 2025)
Learning is a complex process that involves interactions between teaching and learning, and is influenced by various factors such as motivation, self-efficacy, and the relationship between students and teachers. The main goal of education is to produce a generation that is intelligent and has noble character, as well as building good character through effective learning. Students' happiness in learning is an important indicator that influences their motivation and learning outcomes. This happiness can be seen from understanding the material, appreciation from the teacher, and the benefits that students feel from the lessons they receive. However, the joy of learning does not only depend on the learning method, but also on the bonds and relationships that exist between students and teachers. This research uses a qualitative approach with a literature study method. Data was obtained from main sources consisting of books, scientific journals and academic articles that discuss the meaning of happiness in learning. The analysis was carried out by reviewing various relevant literature to gain an understanding of the factors that influence student happiness in learning and their impact on learning outcomes and processes. This research emphasizes the importance of happiness in the learning process to support students' psychological development, as well as increase creativity, motivation and learning outcomes. In conclusion, creating a learning environment that is enjoyable and supports student happiness is very important to achieve the goals of quality education and the formation of student character.